A dam crisis offers a wake-up call on infrastructure. - Sanburn, Josh (Time)
People tend not to think much about their roads, dams and bridges until something goes wrong. The latest reminder of that came in the form of massive rains that swelled California's Lake Oroville to record capacity in early February, threatening to breach the 770-ft. walls of the Oroville Dam. Because of damage in the main spillway, officials muted the water through an unpaved emergency chute--the first time it had been used since the dam was completed in 1968. But the backup spillway almost immediately started to erode, risking the collapse of the spillway's concrete wall and leading the state to order the evacuation of almost 200,000 people who live downstream.